The Effectiveness Of Using Scavenger Hunt On Students’ Vocabulary - Juliana (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2026)
This research aimed to investigate the effectiveness of Scavenger Hunt Technique in students vocabulary to the fifth grade students of Elementary School 22 Mengkudu Kabupaten Sambas in the Academic Year of 2016/2017 and how strong the effectiveness of Scavenger Hunt Technique was for students vocabulary to the fifth grade students of Elementary School 22 Mengkudu Kabupaten Sambas in the Academic Year of 2016/2017. Based on the purposes, the researcher intended to answer these questions ‘’ Is the use of Scavenger Hunt technique effective in vocabulary to the fifth grade students of Elementary School 22 Mengkudu Kabupaten Sambas in the Academic Year of 2016/2017?’’ and How strong is the effectiveness of using Scavenger Hunt technique in vocabulary to the fifth grade students of Elementary School 22 Mengkudu Kabupaten Sambas in the Academic Year of 2016/2017?’’. The researcher was pre experimental research in one pretest-posttest design and had no control group. The researcher used measurement technique as the technique of collecting the data and test as the tool of collecting the data. The primary data of this research was collected from students’ test consisted of 20 questions. The data was analyzed by using descriptive statistic analysis. The population of this research was all of the fifth grade students of Elementary School 22 Mengkudu Kabupaten Sambas in the Academic Year of 2016/2017 consited of 52 students and the sample of this research was five A consisted 24 students taken by using random cluster sampling. The pretest and posttest scores were analyzed by using t test. The result revealed that scavenger hunt technique had positive effect on the students’ memorizing the vocabulary words because the mean score of pre-test and post-test were different and difference was considered significant. The effect size calculation revelead that Scavenger Hunt Technique gave strong effect to the students’ in memori□ing the vocabulary words. It could be inffered that Scavenger Hunt Technique was effective in students vcabulary to the fifth grade students of Elementary School 22 Mengkudu Kabupaten Sambas in the Academic Year of 2016/2017 and the treatment gave strong effect to the students’ in memorizing the vocabulary words. The students must be active in participating in teaching learning process, so they can get the higher achievement in learning, especially in memorizing vocabulary words and the teacher also should be active in teaching learning process so the students can be active in class.